2020
DOI: 10.2147/cmar.s219026
|View full text |Cite
|
Sign up to set email alerts
|

<p>Expression Profiles of DNA Methylation and Demethylation Machinery Components in Pediatric Myelodysplastic Syndrome: Clinical Implications</p>

Abstract: The aim of this study was to analyse the expression profiles of DNMT1, DNMT3A, DNMT3B (components of DNA methylation machinery), TET2 and APOBEC3B (components of DNA demethylation machinery) in pediatric MDS patients and investigate their associations with MDS subtypes, cytogenetics, evolution to acute myeloid leukemia (AML) and p15 INK4B methylation level. Patients and Methods: The expressions of DNMT1, DNMT3A, DNMT3B, TET2, and APOBEC3B were evaluated in 39 pediatric MDS patients by real-time quantitative PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Both too little and too much DNMT expression may play a role in these diseases. Just like Lovatel and colleagues showed that the overexpression of DNMTs plays an important role in pediatric MDS patients developing into AML [25].…”
Section: Discussionmentioning
confidence: 98%
“…Both too little and too much DNMT expression may play a role in these diseases. Just like Lovatel and colleagues showed that the overexpression of DNMTs plays an important role in pediatric MDS patients developing into AML [25].…”
Section: Discussionmentioning
confidence: 98%
“…Preemptive treatment for the minimal residual disease (MRD) is essential for preventing or substantially delaying hematological relapse after HSCT in pediatric MDS, especially in high-risk subgroups. The discovery of genome-wide DNA hypermethylation in pediatric MDS provides a rationale for DNMT inhibitors applicatio n [9,17]. Low-dose decitabine could directly and irreversibly inhibit the DNA methyltransferases.…”
Section: Discussionmentioning
confidence: 99%
“…As for the pre-transplant period for aMDS, a diversity of therapy strategies like intensive chemotherapy, AMLtype induction chemotherapy, minimally myelosuppressive regimen (MMR) and DNA methyltransferase (DNMT) inhibitors has been investigate d [9,10]. Intensive chemotherapy is not generally recommended due to showing no survival benefi t [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown there is increased expression of DNMT3A2 , DNMT3B , and EZH2 in tumors, and transient DNMT3B1 and DNMT3B2 overexpression in primary prostate cells results in increased methylation of some CpG sites that show increased methylation in tumors ( 101 ). Furthermore, in AML, TET2, IDH1, and DNMT3B do not seem to affect each other in terms of methylation pattern and regulation of downstream genes, but IDH1 and DNMT3A do ( 58 , 102 ). More specifically, co-occurrence of DNMT3A and IDH1 mutations show epigenetic patterns different from those of either IDH1 or DNMT3A mutation, upregulation of RAS signaling and unique sensitivity to MEK inhibition and appear to be associated with either worse clinical outcome or show no difference in EFS or OS ( 103 105 ).…”
Section: Molecular Drivers Of Cimpmentioning
confidence: 95%